Aligning Potato Breeding Goals with Citizen Priorities: Insights from Tricot Approach in Nigeria - Sharma, K.; Atieno, E.; Mugo, J.; Sousa, Kauê de; Etten, Jacob van; Nyawade, S. (2024)
This study explored farmers' preferences for potato genotypes using the Tricot (Triadic Comparisons of Technologies) approach. Tricot is a decentralized, participatory approach leveraging farmers' experiences to rank technologies based on agricultural performance and market traits. Plateau State, Nigeria which is typical of many potato-growing areas in Sub-Saharan Africa, was used as the case study. Farmers from varied socioeconomic and demographic backgrounds, selected through local extension agents and agricultural organizations, were provided with trial kits containing three anonymized sets of genotypes labelled options A, B, and C. The anonymity ensured unbiased evaluations. Data collection was conducted across four evaluation phases: vegetative phase 1 (germination, drought tolerance, pest, and disease resistance traits), vegetative phase 2 (extended agronomic trait assessments), harvest phase (yield, tuber appearance, marketability traits), and postharvest phase (dormancy, cooking quality, and ease of sale). At each phase, farmers ranked genotypes based on best and worst traits, with midpoints inferred for complete rankings. The data were recorded using Open Data Kit (ODK), processed through the ClimMob platform (https://climmob.net), and analyzed using R software. The Plackett-Luce model was used to quantify genotype preferences through "worth parameters," with higher logworth values indicating superior performance. Classification and Regression Trees (CART) were used to identify key socioeconomic factors influencing genotype and trait preferences. Principal Component Analysis (PCA) was applied to explore trait-genotype relationships. Farmers' preferences for potato genotypes varied across growth phases. In the vegetative stage, disease resistance, drought tolerance, and germination traits were prioritized. At harvest, market-driven traits: yield, early maturity, and ease of sale became crucial to maximize income and align with market demands. In the postharvest phase, farmers prioritized ease of sale and cooking quality, thus recognizing the strategic advantage of meeting consumer needs and the benefit of delaying sales until off-peak periods to secure higher returns. Genotypes that displayed consistent, desirable traits across all phases, showed overall high logworth probabilities and were preferred for their adaptability to both agronomic and market conditions. Overall, Genotype CIP392797.22 emerged as the most preferred, with a logworth of 0.6, followed by CIP393371.157 (0.26). Moderate preferences were observed for Marabel (0.05) and CIP393371.58 (0.16). CIP381381.13 showed neutrality (0.00), while CIP398208.29 (-0.03) and CIP398190.200 (-0.44) indicated slight to significant aversion, respectively. Household size, age, market distance, education level, and business involvement were identified as the significant socio-economic factors influencing potato genotype preferences. These factors segmented farmers into cohorts based on household size and business involvement. The educated farmers with a business orientation, regardless of household size, favored market-driven traits (ease of sale postharvest, high yield, cooking quality, and early maturity). This cohort of farmers exhibited greater awareness of market trends and agronomic performance, enabling them to make more informed and discriminating decisions. They understood the long-term benefits of choosing genotypes that offer both economic returns and resilience in the face of changing market dynamics. In contrast, subsistence farmers focused on food security, valuing agronomic traits such as disease resistance, drought tolerance, and high yield, while also being mindful of postharvest ease of sale as an indicator of storability. These findings underscore the importance of participatory breeding frameworks in facilitating the integration of citizen preferences. By integrating participatory research with feedback from diverse value chain actors—whether directly or through the farmers, the Tricot approach offers a scalable model for sustainable agricultural development, ultimately accelerating variety adoption across developing countries. Such frameworks could be expanded beyond the farm to include market settings, community-based testing sites, or producer groups, with the goal of focusing on the true end users—consumers, retailers, wholesalers, aggregators, and other stakeholders within the value chain.